Access to health services by lesbian, gay, bisexual, and transgender persons: systematic literature review. Issue 1 (December 2016) - Alencar Albuquerque, Grayce; de Lima Garcia, Cintia; da Silva Quirino, Glauberto; Alves, Maria; Belém, Jameson; dos Santos Figueiredo, Francisco; da Silva Paiva, Laércio; do Nascimento, Vânia; da Silva Maciel, Érika; Valenti, Vitor; de Abreu, Luiz; Adami, Fernando
Abstract Background The relationship between users and health services is considered essential to strengthen the quality of care. However, the Lesbian, Gay, Bisexual, and Transgender population suffer from prejudice and discrimination in access and use of these services. This study aimed to identify the difficulties associated with homosexuality in access and utilization of health services. Method A systematic review conducted using PubMed, Cochrane, SciELO, and LILACS, considering the period from 2004 to 2014. The studies were evaluated according to predefined inclusion and exclusion criterias. Were included manuscripts written in English or Portuguese, articles examining the Lesbian, Gay, Bisexual, and Transgender population's access to health services and original articles with full text available online. Results The electronic databases search resulted in 667 studies, of which 14 met all inclusion criteria. Quantitative articles were predominant, showing the country of United States of America to be the largest producer of research on the topic. The studies reveal that the homosexual population have difficulties of access to health services as a result of heteronormative attitudes imposed by health professionals. The discriminatory attendance implies in human rights violations in access to health services. Conclusions The non-heterosexual orientation was a determinant factor in the difficulties of accessing health care. A lot must still be achieved to ensure access to health services for sexual minorities, through the adoption of holistic and welcoming attitudes. The results of this study highlight the need for larger discussions about the theme, through new research and debates, with the aim of enhancing professionals and services for the health care of Lesbian, Gay, Bisexual, and Transgender Persons.